Attitude Towards Use and Behavior Intention of Online Art Appreciation Courses in Public Universities in Yunnan, China - Lin, Peng; Xiang, Chaochu; Leelakasemsant, Charnsid (Scholar: Human Sciences, 2023)
Purpose: This study developed a model to predict the key factors affecting the behavior intention to adopt online art appreciation courses of undergraduate students. Key variables are perceived ease of use, perceived usefulness, performance expectancy, perceived satisfaction, effort expectancy, attitude towards use and behavioral intention. Research design, data and methodology: The proposed model was empirically tested by collecting data from 498 undergraduates in three public universities in Yunnan, China. The sampling techniques were judgmental, quota and convenience samplings. Before the collection of the data, the Item Objective Congruence (IOC) Index and Cronbach’s Alpha were used to approve measuring items and constructs’ reliability. Data were analyzed by testing the measurement and structural models by Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM), which included goodness of model fits, correlation validity, and reliability. Results: Performance expectancy has the strongest impact on behavior intention, followed by attitude towards use and effort expectancy. Perceived usefulness and perceived ease of use significantly influence attitude towards use. On the other hand, perceived satisfaction has no significant influence on behavioral intention. Conclusions: To the best of this findings, this study attempts to explore students’ attitude towards use and behavioral intention to adopt online art learning in order to improve their learning efficiency.